Cognitive impact of virtual reality sketching on designers' concept generation. Issue 2 (2nd April 2020) - Yang, Eun Kyoung; Lee, Jee Hyun
ABSTRACT: This study focuses on identifying the cognitive impact of virtual reality (VR) sketching on the concept generation phase of the design process. For an empirical study to analyse the cognitive influence of VR sketching, we conducted a pilot study for empirical research based on the protocol analysis of designers' cognitive activities in VR sketching and compared the results with those of traditional sketching. Spatial inspection was a key behavioural factor of VR sketching when considering its high-frequency repetitive and continuous interactions with a designer's representation activities throughout the concept generation process. The cognitive impact of VR sketching revealed the following decisive features: extension of solution space, enhancement of idea transformation and inducement to a holistic design approach for concept generation. These findings provide insight for understanding the cognitive role of advanced digital design tools for future design research.